Análise técnico-econômica-ambiental da produção de nanocelulose em biorrefinarias de cana-de-açúcar - Batista, Gustavo (2021)
The production of ethanol, sugar and energy in Brazilian sugarcane biorefineries generates a large number of residues, such as bagasse and straw. An alternative is the reuse of these residues as feedstock for obtaining cellulose nanomaterials, high valueadded biomaterials with innovative applications in several sectors and projection of great market growth in the coming years. However, the economic and environmental potential of nanocellulose production technologies from sugarcane residues still need to be evaluated to subsidize investments in this sector. Thus, this work aims to evaluate the technical, economic and environmental feasibilities of different process routes for obtaining cellulose nanomaterials in a process unit attached to a sugarcane biorefinery. For this, process modeling and analysis tools were applied, using previous data obtained in literature and field experts’ information. Mass and energy balances were developed for different Case Studies. The economic feasibility of these scenarios was evaluated by calculating the MPSP (Minimum Product Selling Price) of nanocellulose that reaches the Minimum Acceptable Rate of Return (MARR) arbitrated for the investment. In turn, the Life Cycle Analysis of the processes indicated the technologies with the lower environmental impacts. It is expected that this work generates results that indicate investment opportunities for sugarcane biorefineries that plan to diversify their product portfolio. Furthermore, researchers will be able to use the results to focus efforts on optimizing the most viable routes towards increasing the productive potential of the nanocellulose industry.